General health status and psychological impact of COVID19 pandemic and curfew on children aging 3 to 12 years - Shamsah, Abdullah; Aburezq, Maryam; Abdullah, Zahraa; Khamissi, Fatemeh; Almaateeq, Batool; AlAlban, Fatima; Almashmoom, Sarah; Ziyab, Ali (Frontiers in Child and Adolescent Psychiatry, 2022)
Background COVID-19 is an infectious disease that was declared as a pandemic and public health emergency in late 2019 and has impacted children's mental health worldwide. This study aimed to assess the general and mental health status of children during different stages of COVID-19 pandemic, and to identify the associated factors. Methods A cross-sectional study conducted on children aging 3 to 12 years in Kuwait during three different stages of COVID19 pandemic (pre-total curfew, during total curfew, and post-total curfew). The psychological status was assessed using the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders criteria. Results Of 2157 children between the age of 3 to 12 years old, 853 (39.5%) reported increased level of aggression, 789 (36.6%) over-crying, 749 (34.7%) sadness, 493 (22.9%) anxiety, 429 (19.9%) anhedonia, 383 (17.8%) confusion, 274 (12.7%) nightmares, 177 (8.2%) avoidance, 174 (8.1%) physical symptoms and 121 (5.6%) bedwetting during the pandemic. General health status was also affected with reported disturbed sleeping pattern (84.6%), altered appetite (50.9%) and weight changes (36.9%), mainly weight gain. Risk factors included being non-national, as well as having lower parental educational level and lower socioeconomic status; while protective factors involved meeting classmates, indoor and outdoor activities, and less screen time. Conclusions COVID19 crisis had drastic impact on children's mental and general health, requiring serious action regarding evaluating this generation and intervening accordingly.